A qualitative study investigating the impact of high schools on identity formation in a South African context - Smith, Dayna (The IIE, 2020)
The study was conducted based on the lack of available literature found that explored identity formation in the school context. Educational institutions are prevalent societal structures and therefore have the potential to be influential based on the number of learners that could be shaped by school practices and interactions. The majority of the available literature found appeared to be quantitative and therefore provided motivation for a qualitative study on identity formation in the South African high school context. The research problem was that the available literature appeared to be theoretical and did not clearly define the role of institutions in the formation of identity. Three participants were used and semistructured interviews were conducted which allowed participants to answer questions about their experiences with identity formation in high school. The role of teachers, a multicultural education, adolescence, peer interactions, and friendships proved to be significant in impacting identity formation. The exploration of these factors contributed to the existing body of knowledge and provided insight into identity formation in South African high schools. The findings encourage further research on this topic in the South African context and provide insight for high schools as the importance of supporting learners in their identity formation through adolescence was significant.
Keywords: High school; Identity formation; South Africa